Clinical trials using functional foods provide unique challenges. (June 2018) - Brown, Lindsay; Caligiuri, Stephanie P.B.; Brown, Dan; Pierce, Grant N.
Highlights: Organizing and running a clinical trial using functional foods (FF) is unique. Trials using FF have different challenges than conventional drug trials. This paper identifies 13 important technical parameters unique for FF trials. Awareness of these items will insure FF data will be as valuable as drug trials. Abstract: Clinical trials usually evaluate medicines as the intervention of choice to improve health. Changing the intervention to a functional food would appear straightforward, but there are many unique technical issues that will confront the Principal Investigator and research team. These challenges are found in each of the three distinct phases of a trial: the initial organisation of the trial, running the trial, and finally, the dissemination of the data following successful completion of the trial. Each challenge presents very different issues that will limit the conclusions of the trial unless addressed properly. We suggest that careful planning of the trial taking into consideration thirteen important technical parameters can ensure that the data are relevant and lead to reliable conclusions, every bit as valuable as those obtained in trials with medicines.